Bayesian model updating with consideration of modeling error - Zhang, Erliang; Feissel, Pierre; Antoni, Jérôme (European Journal of Computational Mechanics, 2010)
On account of measurement and modeling errors, structural identification is better tackled within the statistical framework. In this work, a complete process of Bayesian inference for the characterization of the dynamic behavior of a linear structure is presented in the frequency domain. The polynomial chaos expansion is adopted as a surrogate model to propagate the parameter uncertainty and thus accelerate the evaluation of their posterior probability distribution. Moreover, one hybrid modal model is proposed by introducing some additional variables so as to deal with the modeling errors. Bayesian updating is validated experimentally on a steel square plate and the proposed hybrid modal model is illustrated numerically on a cantilever beam.